A new species of Mesochaetopterus (Annelida, Chaetopteridae) from Hong Kong, with comments on the phylogeny of the family - Zhang, Yanjie; Rouse, Greg W.; Qiu, Jian-Wen (Zootaxa, 2015)
We described a new species, Mesochaetopterus tingkokensis, based on 14 specimens collected from an intertidal area in Hong Kong. This species is large (body length of complete specimens 17.9–24.1 cm), with 9, 2 and 36–41 chaetigers in region A, B and C, respectively. It belongs to a small group of Mesochaetopterus species with an expanded wing-shaped notopodia in chaetiger B2. The new species can be distinguished from other Mesochaetopterus species in this group by having a pair of palps with two longitudinal stripes formed by suture-like discontinuous orange bands, more teeth in the uncini of region B and C neuropodia, and presence of a bundle of simple chaetae in region C notopodia. Comparison with other chaetopterids based on partial cytochrome oxidase I (COI), 18S and 28S rRNA gene sequences confirmed the placement of M. tingkokensis n. sp.within Mesochaetopterus and its distinction from other members of this genus with the available DNA sequences. The phylogenetic tree base on COI showed that Mesochaetopterus and Chaetopterus are paraphyletic, but that based on concatenated data, 18S and 28S showed they are monophyletic with low supporting values.